Hubert Lenoir et les révélations de l’affliction - Leguerrier, Louis-Thomas (Sens public, 2019)
Quand Hubert Lenoir, lors de son entrevue à Tout le monde en parle, a déclaré : « J’ai un peu le goût de me crisser en feu ces temps-ci », s’attirant les remontrances des animateurs qui jugeaient de mauvais goût le fait de dire une telle chose à la télévision, et de surcroît sur un plateau où se trouvait un invité ayant déjà fait une tentative de suicide, cela a provoqué un certain émoi dans le public, et on reprocha d’un côté au chanteur de banaliser le suicide et de l’autre aux animateurs d’avoir banalisé la détresse peut-être tout à fait sérieuse de celui-ci. Plutôt que de prendre part à ce débat, ou encore de proposer des stratégies pour briser les tabous au sujet du suicide, je voudrais aborder la dimension littéraire de ce fameux malaise télévisuel, qui est liée au malaise de l’époque contemporaine face à ce que j’appellerai ici la mise en scène de l’affliction.
Keywords: Hubert Lenoir; Susan Sontag; affliction; impudeur; indecency; literary; littéraire

“Saw You in the Dark”: Exploring Rufus Wainwright’s Emotional Vulnerability in Fan-Captured Live Performance Videos - Salerno, Stephanie (Performance Matters, 2019)

True Loves, Dark Nights: Queer Performativity and Grieving Through Music in the Work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)

Rufus Wainwright - Williams, Katherine (Equinox Publishing, 2016)
Canadian-American singer-songwriter Rufus Wainwright is famous around the world for his multi-faceted musical style, shown through both his recorded output and his engaging live performances. Katherine Williams combines aspects of his life story with scholarly readings drawn from several methodologies.

Rufus Wainwright sings "Grey Gardens": on Thomas Mann's "Death in Venice", Tadzio and his pop cultural "life" - Bałżewska, Katarzyna (Beyond Philology: An International Journal of Linguistics, Literary Studies and English Language Teaching, 2015)

Michel Louvain. Sans âge - Gignac, Benoît (Éditions Caractère, 2014)
Découvert au milieu des années 50, admiré et adulé, Michel Louvain fait encore battre les coeurs près de 60 ans après avoir amorcé sa carrière. Ce livre-coffret retrace le parcours irréprochable de cet artiste accompli, qui a remporté les honneurs autant pour ses performances sur disque, sur scène et à la télévision que pour son soutien à des causes sociales.

"The Cult of the Diva" – Rufus Wainwright as Opera Queen - Smith, Oliver C. E. (Transposition. Musique et Sciences Sociales, 2013)
The music of Rufus Wainwright has been afforded much critical acclaim thanks to the singer-songwriter’s understanding of Queer cultural history, and the candor with which he explores (homo)sexuality in his music. This case study seeks to examine his use of opera in particular, and how Wainwright uses the historical trope of the opera queen to incorporate his own queerness into music, thus asserting an authority of difference and challenging the dominant (hetero)norm constructions of masculinity in popular music. Wainwright disregards any cultural framework imposed by heternormativism, and reclaims the Orphic figure of operatic authority as one of queer power through this absence. By drawing on his own relationship with opera, Wainwright exploits the right this gives him by reinterpreting cultural history, and revising the pejorative stereotype that is an opera queen.
Keywords: Eurydice; Hallelujah; Jeff Buckley; Memphis Skyline; Rufus Wainwright; Waiting For A Dream; Want Two; diva; gay; heteronormativism; identity; masculinity; opera; queer; stereotype

De l’ombre à la lumière : fragments pour une analyse des trois premiers albums d’Ariane Moffatt - Doyon, Noémie (Canadian Folk Music, 2012)

Femme-acrobate, femme-automate : Le Fil de Camille et Le Cœur dans la tête d'Ariane Moffatt - Doyon, Noémie (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2012)
La moustache de Brassens, la robe noire d'Edith Piaf, les paillettes de Claude François, les cheveux de Dalida ... Les chanteurs ont un corps indissociable de leurs chansons. Ce livre s'intéresse à la présence physique de la musique populaire, à sa performance sur scène et sur le disque. Voici observées les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale

Entre stabilité et mouvement : l'oscillation spatiale dans le diptyque "Want" de Rufus Wainwright - Mathieu-Lessard, Jeanne (Université Laval, 2011)
Ce mémoire propose l’analyse de chansons extraites du diptyque Want (formé des albums Want One et Want Two), de l’auteur-compositeur-interprète Rufus Wainwright, en regard des relations entre l’énonciateur et l’espace. La notion d’oscillation spatiale, définie en introduction, est au cœur de la situation de l’énonciateur et se déploie sous de multiples formes dans les cinq chansons à l’étude. « Oh What a World » et « I Don’t Know What It Is » sur Want One, « Hometown Waltz », « Memphis Skyline » et « Old Whore’s Diet » sur Want Two, ont été choisies pour la façon dont la relation à l’espace y agit de même que pour leur emplacement dans l’ensemble. La position de l’énonciateur mise en évidence dans chaque analyse s’inscrit au sein d’un parcours, que l’étude préliminaire du paratexte des albums aura d’ailleurs mis en évidence.

Performing ‘Judy’: The Creation and Function of Cover Personae in Popular Music in Rufus Wainwright's Judy Garland Concerts - O'Connell, Sam (Contemporary Theatre Review, 2011)

One Day in the Life of Rufus Wainwright - Hailand, Tim (Hailand Books, 2010)
One Day in the Life of Rufus Wainwright follows the singer-songwriter from New York City to Boston for his performance at the Boston Opera House, which featured his sister Martha Wainwright as a special guest. With an intro by NYC nightlife legend Cherry Vanilla and text from Rufus himself.

There Will Be Rainbows: A Biography of Rufus Wainwright - Lake, Kirk (Itbooks, 2010)
"No contemporary pop performer's work mixes innovation and tradition like Rufus Wainwright's. He is the son of singer, songwriter, actor Loudon Wainwright III and legendary Canadian folk singer Kate McGarrigle whose story is one of towering highs and rock bottom lows in which family influences, sexual experimentation, and a crystal meth addiction in the early 2000s have greatly contributed."

“Oh What a World”: Queer Masculinities, the Musical Construction of a Reparative Cultural Historiography, and the Music of Rufus Wainwright - Schwandt, Kevin C. (Université du Minnesota, 2010)
Throughout his ascendancy in fame and cultural visibility, singer/songwriter and gay pop icon Rufus Wainwright's output has been consistently related, by scholars and critics alike, to camp aesthetics, modes of artistic expression typically understood as emerging from queer communities, particularly certain gay male populations, but ones whose political potential is highly contested. Traditional conceptions of camp, as most famously articulated by Susan Sontag in the 1960s, emphasize style over content, necessarily rendering it politically-disengaged. However, scholars have vehemently challenged conceptions like Sontag's, in order to reclaim camp as a potent means to facilitate queer world-making and a powerful resistance to heteronormativity. I examine Wainwright's image and music in order to theorize a new queer interpretive listening position. Specifically, I draw upon the literary perspective of “reparative reading,” articulated by Eve Kosofsky Sedgwick in opposition to what she describes as “paranoid reading,” to propose a uniquely queer approach to musical and cultural historiography, exemplified by Wainwright's music. Much of the current queer musicology focuses on lost histories, systematic marginalization, and the commoditization of queer identities. While such approaches have produced important insights, thorough examination of the relationships between queer cultural products and their queer reception has proven elusive. This project suggests a unique approach to understanding the musical construction of a specific kind of queer masculinity, one which combines authorial creation with reparative conceptions of reception, in order to theorize a uniquely gay male interpretive position. When viewed through a theoretical lens combining politically-potent conceptions of camp performativity with a reparative reading position, Wainwright's music strikingly enacts Philip Brett's call to claim, not historical evidence, but the right of interpretation, emerging as an act of resistance via the reclamation and consolidation of a queer interpretive authority. In this way, Wainwright articulates both a rupture in the history of queer masculinity and a powerful means of resistance to the often-exclusionary relationships between literary, musical, and artistic objects and the heteronormative cultural systems in which they are created.
Keywords: Communication and the arts; Gay history; Gay rights; Historiography; Masculinities; Popular culture; Queer; Reparative reading; Rufus; Social sciences; Wainwright